ROLE OF CARBON DOTS AND THEIR APPLICATIONS IN AGRICULTURE - Manoj; Chauhan, Sonu (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Carbon Dots exhibit exceptional size-dependent optical properties that can be adjusted through surface alterations, thus broadening their applicability across various domains. Furthermore, their facile synthesis, excellent dispersibility, solubility, hydrophilic characteristics, biocompatibility, environmental sustainability, cellular permeability, low toxicity, high photostability, and cost-effectiveness have garnered interest across a wide range of applications, from materials chemistry to nanotechnology. Carbon Dots have long been utilized as growth enhancers by improving the photosynthesis process in agricultural systems. In this approach, the manufactured Carbon Dots of the specified size are distributed on the plant, where the leaf adsorbs the CDs onto its surface. Consequently, Carbon Dots enhance the absorption rate of sunlight and carbon dioxide. Consequently, the rate of photosynthesis escalates. Consequently, the crop’s growth and yield may rise by 10%-20%. Moreover, Carbon Dots possess disease-resistant qualities that safeguard them against many ailments. The substantial incorporation of Carbon Dots in plants significantly enhances seed germination, root development, leaf quantity, and enzymatic activity for the conversion of CO2 into carbohydrates via an accelerated rate of photosynthesis. Consequently, rice crop productivity rises by 14.8%. Furthermore, it possesses disease resistance that safeguards plants from damage. Moreover, Carbon Dots can transform detrimental UV light into photosynthetically active radiation, hence promoting enhanced plant growth. This study elucidates the physiological roles of carbon dots in crop growth and development, photosynthesis, and their uses in enhancing agriculture.